(In)disciplina escolar : uma abordagem psicológica - Zenni, Cristine de Bragança (2012)
This study aims at investigating the issue (in) school discipline from a psychological understanding and critical of its formation and development as well, aims to find alternatives to assist in teaching proper treatment of this phenomenon. Through a bibliographical study are exposed in the first chapter some historical views on the subject of discipline / indiscipline, starting with the pre-history, through the ancient period, Middle Ages, Modern Ages (Renaissance absolutism, rationalism) to the Contemporary. The second chapter is appealing to the world of psychological studies related to (in) school discipline pausing, especially reading some authors that deal with the issue in order to elucidate the following questions: why the discipline has a malaise so intense in school today? What is discipline and how it is identified in school? What are the most common behaviors considered disruptive? Key psychological and psychosocial factors that trigger disruptive school? Indiscipline can be considered a disease? Under what circumstances indiscipline is considered a pedagogical problem and when it should be addressed as a matter pathology? Finally, the third chapter dwells on the theory of maturation in which Winnicott then the search moves from the fields of Psychology and Pedagogy in the investigation of theoretical elements able to gain a better understanding of the phenomenon of (in) discipline in schools nowadays, as it aims to list contributions that psychology can offer Pedagogy in confronting the problem of indiscipline in school